A Patient With Focal Myositis and Primary Cutaneous Diffuse Large B-Cell Lymphoma: A Case Report - Wu, Quanxin; Xu, Cheng; Wang, Li (Frontiers in Oncology, 2021)
We report a rare case of a 92-year-old male, with a history of statin/ezetimibe intake, complained of pain and swelling of left forearm. The patient was diagnosed with focal myositis at first. Symptoms aggravated after 2 months of immunomodulatory therapy, and accompanied with protrusion lesion at left elbow. Biopsy of the protrusion lesion turned out to be primary cutaneous diffuse large B-cell lymphoma.